Manajemen Strategi Pesantren Dalam Pendidikan Berbasis Transformasi Budaya Dan Politik - Siti Sri Istiqamah (UIN Mataram, 2021)
Pesantren has strong religious and social characteristics. Historically, pesantren have lived with the community, especially in rural areas. This fact brings this institution closer to the problems that occur in the social environment. Problems of poverty, limited access to information, knowledge, marginalization make rural communities live in powerlessness. Pesantren education is the main focus because it is close, cheap and can be trusted to change through religious knowledge. Even though in the end the community felt that it was not enough to just receive an Islamic boarding school education, they continued to have traditions and knowledge similar to those of the institution, namely Islamic higher institutions.